Synthesis of Hydroxyapatite from Snail Shells Using the Precipitation Method - rahel aditya amara putri; moh rifqi maulana; erwan adi saputro; caecillia pujiastuti; Ni ketut sari (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Hydroxyapatite (HA) is a bioceramic widely used in biomedical applications due to its excellent biocompatibility and bioactivity. This study aims to synthesise hydroxyapatite from rice field snail shells (Pila ampullacea) using the precipitation method and to evaluate the effects of phosphoric acid (H?PO?) concentration and heating time on the synthesised hydroxyapatite's characteristics. The synthesis was conducted by varying H?PO? concentration from 0.25 to 2 M and heating time from 1 to 3 hours at a calcination temperature of 800°C. The resulting hydroxyapatite was characterized by SEM-EDX, XRF, XRD, and FTIR analyses, and the Ca/P ratio was optimized using Response Surface Methodology (RSM). SEM-EDX analysis revealed porous and agglomerated surface morphology, indicating successful thermal decomposition of calcium carbonate into calcium oxide precursor. XRF results showed that increasing H?PO? concentration and heating time significantly reduced the Ca/P ratio toward the stoichiometric value of hydroxyapatite (1.67), with optimum conditions achieved at 1.5–2 M H?PO? and 2–2.5 hours heating time. XRD analysis confirmed the formation of crystalline hydroxyapatite with an average crystal size of 14.62 nm and crystallinity degree of 81.23%. FTIR spectra identified characteristic phosphate functional groups, confirming hydroxyapatite formation. The RSM optimization demonstrated that both H?PO? concentration and heating time significantly influence the Ca/P ratio. These findings indicate that rice field snail shells have strong potential as a sustainable and cost-effective alternative calcium source for hydroxyapatite synthesis in biomaterial applications. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-BeingSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and Production